Kant and the horizons of the critical philosophy - Ples, Marta (Folia Philosophica, 2008)
Book review: Questions and Perspectives of Transcendentalism. On the 200th anniversary of Immanuel Kant's death. Ed. A.J. Noras. Katowice: University of Silesia Press, 2006.